COVID-19 Crisis Management: Lessons From the United Arab Emirates Leaders - Abbas Zaher, Walid; Ahamed, Faheem; Ganesan, Subhashini; Warren, Katherine; Koshy, Ashish (Frontiers in Public Health, 2021)
This study analyses the UAE leadership's approach in response to the COVID-19 crisis through the Organization for Economic Co-operation and Development's Strategic Crisis Management Framework. This framework analyzes the crisis management in three phases: the preparedness, the response to mitigate damage and the feedback mechanism after the crisis. The analysis showed that the key components of the UAE's crisis management included efficient and able governance, integrated utilization of public-private partnerships and a global workforce of excellence. As a result, the UAE now ranks among the top 10 countries worldwide for its leadership and proactive approach during the COVID-19 pandemic, according to Global Response to Infectious Diseases Index. The SWOT analysis on the response toward COVID-19 crisis management helped in critically analyzing and understanding the UAE's unified and systematic response to the pandemic, which provides developing and developed countries alike a new high standard for leadership and effective public health management.